A green synthetic method for cobalt(II,III) oxide nanoparticles with high surface activity - Ya. Absalan; R. Alabada; M. R. Razavi; M. Gholizadeh; O. V. Avramenko; I. N. Bychkova; O. V. Kovalchukova (Тонкие химические технологии)
Objectives. To develop a new green method for the synthesis of nanosized materials of cobalt(II,III) oxide, with improved surface activity, using environmentally friendly precursors and solvents.Methods. A green method was proposed, in order to isolate Co3O4 nanoparticles with high surface activity. Instead of the usual organic solvents, three different natural sugars, including glycogen, sucrose, and glucose were used for the first time as templates. Water as a green solvent was used in all the steps. The polymorphic composition of the synthesized samples was determined by means of X-ray phase analysis. The morphology of the obtained crystallites was studied from micrographs of the oxide phases. Image Pro Plus 6 software was used to measure the size of nanoparticles. The surface activity of the isolated samples was studied using the Brunauer–Emmett–Teller method and the Langmuir method. The Barret–Joyner–Halenda method was used to determine the diameter, volume, and distribution of pores.Results. The crystallite sizes of the samples are 23 nm, 36 nm, and 30 nm for glucose, glycogen, and sucrose templates, respectively. Adsorption–desorption isotherms for samples obtained from complexes of glucose and sucrose correspond to type IV, indicating a strong interaction between the adsorbent and the adsorbed sample. The isotherm for the sample isolated from the complex with glycogen is of a different type and most likely indicates that this sample is almost completely mesoporous. The pore radii are found in the interval 1.2–1.6 nm.Conclusions. A new green method for the synthesis of nanosized particles of Co(II,III) oxide using natural saccharides and deionized water was developed. The composition, morphology, structure, and surface activity of the samples obtained were studied. It was shown that due to the polymeric structure of their metal complexes and the ability to bind active carbon on the surface of nanoparticles, natural saccharides can be used as matrices in the synthesis of nanosized metal oxides with high surface activity.